Hubungan antara Asupan Magnesium dan Kekuatan Genggam pada Lansia - Putra, Muhammad Iqbal Arigi; Herwana, Elly (Jurnal Biomedika dan Kesehatan, 2023)
Background Elders experience an aging process that is marked by a decrease in muscle mass that can result in a decrease in overall muscle strength.  Handgrip strength is a parameter used to assess maximum handgrip which can represent an overall muscle strength. Magnesium has a role for skeletal muscles and also affects muscle performance. This study aims to measure the relationship between magnesium intake and handgrip strength in the elderly. Methods This study is an observational analytical study with a cross-sectional design, involving elders aged  60 years in elderly nursing homes as the study subjects. Elders who were able to communicate actively were included and elders who had physical disability were excluded. The Semi Quantitative Food Frequency Questionnaire (FFQ) was used for assessing magnesium intake and handgrip strength was measured using a handgrip dynamometer. Data were analyzed with Chi-Square statistical test and Fisher’s Exact Test with a significance of < 0.05. Results A group of 71 elders participated in this study. The result of this study shows that subjects with sufficient magnesium intake amounted to 18 subjects (25.4%) and 53 (74.6%) with low magnesium intake.  The distribution of subjects with sufficient handgrip strength amounted to 36 subjects (50.7%) and 35 (49.3%) with low handgrip strength.  Statistical analysis shows that there is no significant relationship between magnesium intake and handgrip strength in elders (p=0.539; p>0.05), while sociodemographic factors of age and gender showed a significant relationship towards handgrip strength (p=0.012 and p=0.028; p<0.05). Conclusions There is no significant relationship between magnesium intake and handgrip strength in elders.  Sociodemographic factors of age and gender showed significant relationships towards handgrip strength.